SMOKING PREVALENCE IN ACUTE MYOCARDIAL INFARCTION PATIENTS WITH SUDDEN DEATH RISK - K. A. Kireev; A. A. Fokin; G. E. Kramnik (Кардиоваскулярная терапия и профилактика)
Aim. To assess the smoking prevalence in myocardial infarction patients (MI).Material and methods. The questioning of 200 patients with MI diagnosis was performed, age 32-65 y.o., mean age 50,4±1,4 y.o. All participants were Chelyabinsk citizens, or neighborhood inhabitants. Respondents were asked questions on their social status and smoking.Results. For the smoking, following responses were gathered: nonsmokers — 41,0%; former — 10,0%; long time smokers — 45,0%; recent smokers — 4,0%. Smoking was significantly (p<0,05) more prevalent in males — 61,1% vs 26,1%. Thirty six point four percent replied that started smoking at the age ≤15 y.o.; 54,2% — at the age 16-20 y.o. and 9,4% — older than 20 y.o. Among responders, 20,4% smoke 10 cig. daily; up to 1 pack daily — 16,3%; one pack daily — 37,8%; >1 pack — 25,5%. During the last year, 31,6% tried to quit. Motivations for the attempt were: negative influence of health — 60,0%; relatives and friends convincing — 25,0%; healthcare specialist convincing — 15,0%; the treating clinician prohibited to smoke — 0%.Conclusion. In MI patients mostly of economically active age, living in a large industrial city, the prevalence of smoking is high (49,0%) as its intensity. Among the category of patients, there was insufficient awareness on the negative influence of modifiable risk factors on the development of cardiovascular pathology. By the subjective estimation, only 26,0% responders with MI associated its development with improper lifestyle, and 5,5% — with smoking.